Optimization and performance criteria of a Stokes polarimeter based on two variable retarders - Peinado, Alba (2010)
In this paper we present the analysis, optimization and implementation of several Stokes polarimeter configurations based on a setup including two variable retarders. The polarimeter analysis is based on the Mueller-Stokes formalism, and as a consequence, it is suitable to deal with depolarized light. Complete Stokes polarimeters are optimized by minimizing the amplification of simulated errors into the final solution. Different indicators useful to achieve this aim, as the condition number or the equally weighted variance, are compared in this paper. Moreover, some of the optimized polarimeters are experimentally implemented and it is studied the influence of small deviations from the theoretical ones on the amplification of the Stokes component error. In addition, the benefit of using incomplete polarimeters, when detecting specific ranges of states of polarization, is discussed